Vapor grown carbon nanofiber based cotton fabrics with negative thermoelectric power - Paleo, A. J. (2020)
Vapor grown carbon nanofiber (CNF) based ink dispersions were used to dip-coat woven cotton fabrics with different constructional parameters, and their thermoelectric (TE) properties studied at room temperature. Unlike the positive thermoelectric power (TEP) observed in TE textile fabrics produced with similar carbon-based nanostructures, the CNF-based cotton fabrics showed negative TEP, caused by the compensated semimetal character of the CNFs and the highly graphitic nature of their outer layers, which hinders the p-type doping with oxygen groups onto them. A dependence of the electrical conductivity (r) and TEP as a function of the woven cotton fabric was also observed. The cotton fabric with the largest linear density (tex) showed the best performance with negative TEP values around - 8 lV K-1 , a power factor of 1.65 9 10-3 lW m-1 K-2 , and a figure of merit of 1.14 9 10-6 . Moreover, the possibility of a slight e- charge transfer or n-doping from the cellulose onto the most external CNF graphitic shells was also analysed by computer modelling. This study presents n-type carbon-based TE textile fabrics produced easily and without any functionalization processes to prevent the inherent doping with oxygen, which causes the typical p-type character found in most carbon-based TE materials